2011
DOI: 10.1179/1743132810y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

In vitroculture and characterization of oligodendrocyte precursor cells derived from neonatal rats

Abstract: Demyelination prevents recovery of neural function following SCI. Demyelination has already become a potential therapeutic target for this insidious and challenging problem. The In vitro culture and biological characteristics of OPCs are fundamental and necessary for further investigation of cell transplantation in vivo. Growth pattern, differentiation and proliferation are very vital for therapeutical effects of OPCs following transplantation after SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, A2B5 immunoreactivity (a marker for precursor cells developing into type II astrocyte and oligodendrocytes) was not detectable in rat and mouse astrocyte cultures at 28 and 42 DIV (Table 4). The low abundance of neurons and oligodendrocytes in our cultures can be attributed to the fact that (i) neurons do not grow on non-coated dishes or coverslips, and need further supplements in addition to the vitamins and non-essential amino acids in DMEM and (ii) oligodendrocytes normally grow on the surface of the astrocyte layer (Wu et al, 2011) and are washed away during the multiple PBS washing steps 24 h after seeding and during passaging. The high purity of cortical rat astrocyte cultures with Table 4 The signal intensities of the immunoreactivity and the amount of cells positively stained for GFAP, vimentin, nestin, S100␤, GLAST, GLT-1, mGluR1, mGluR2/3, and A2B5 in mouse and rat astrocyte cultures after 28 and 42 DIV.…”
Section: Tablementioning
confidence: 98%
“…In addition, A2B5 immunoreactivity (a marker for precursor cells developing into type II astrocyte and oligodendrocytes) was not detectable in rat and mouse astrocyte cultures at 28 and 42 DIV (Table 4). The low abundance of neurons and oligodendrocytes in our cultures can be attributed to the fact that (i) neurons do not grow on non-coated dishes or coverslips, and need further supplements in addition to the vitamins and non-essential amino acids in DMEM and (ii) oligodendrocytes normally grow on the surface of the astrocyte layer (Wu et al, 2011) and are washed away during the multiple PBS washing steps 24 h after seeding and during passaging. The high purity of cortical rat astrocyte cultures with Table 4 The signal intensities of the immunoreactivity and the amount of cells positively stained for GFAP, vimentin, nestin, S100␤, GLAST, GLT-1, mGluR1, mGluR2/3, and A2B5 in mouse and rat astrocyte cultures after 28 and 42 DIV.…”
Section: Tablementioning
confidence: 98%
“…To promote cell proliferation and oligodendrocyte lineage phenotype, in the following study, isolated cells were cultured directly in serum-free medium supplemented with PDGF-AA and bFGF for the first 3 days after seeding. After treatment with the aforementioned mitogens, OPCs are characterized by a small size (6–12 µm in the case of neonatal rat cells), a clearly visible, rounded cell body, the presence of few processes and a high proliferation capacity (Wu et al 2011 ). We showed that supplementation of culture medium with PDGF-AA and bFGF significantly increases the proportion of progenitor cells and cells at the initial stages of differentiation in culture.…”
Section: Discussionmentioning
confidence: 99%